The Selfish Gene
Richard Dawkins\\\' theories have helped change the whole nature of the study of social biology. In this book, Dawkins shows how the world of the selfish gene revolves around savage competition and deceit, and yet, acts of apparent altruism do exist in nature. Bees, for example, will commit suicide when they sting to protect the hive, and birds will risk their lives to warn the flock of an approaching hawk.